THE URGENCY OF CALLIGRAPHY IN ISLAMIC EDUCATION - Maryam Hafizhah; Sayed Muhammad Ichsan (Yayasan Haiah Nusratul Islam, 2024)
This study aims to describe the urgency of calligraphy in Islamic education. In Islamic education, calligraphy is one of the important components in developing students' character. This is seen in the use of calligraphy to teach and assist students in producing scholarly works that reflect an awareness and deep understanding of Islamic teachings.The method used is a literature study, by collecting data from books, previous research results, journals, and related articles. The results of the study show that calligraphy has a very clear urgency in Islamic education, both in terms of aesthetics and spirituality. Calligraphy art is not only a form of visual art, but also a means to understand and respect the Qur'an. Therefore, the integration of calligraphy in Islamic education is very important to enrich the understanding and appreciation of religious teachings. In addition, Calligraphy is very important in Islamic art because it is a form of “embodiment” of the holy words of Allah SWT.